PREPARING PRE SCHOOL–CHILDREN WITH SENSORIAL AND PRACTICAL LIFE CLASS - Anggini, Wulan Yulian; Harmoko, Danang Dwi; Bakhtiar, Ahmad (Research and Development Journal of Education, 2024)
This study explores the critical role of early childhood education in nurturing sensory and practical life skills within preschool classrooms. Focusing on the Montessori method, the research examines how experiential learning and activities closely tied to everyday life can significantly benefit preschool-aged children. The Montessori approach prioritizes hands-on engagement, allowing children to develop fine motor skills, sensory awareness, and practical abilities that are essential for fostering independence. These foundational skills are not just about mastering basic tasks; they are integral to broader cognitive, social, and emotional development. The study emphasizes how well-structured sensory and practical life activities enable children to explore their environment, develop problem-solving abilities, and gain confidence in their capabilities. By participating in such programs, children demonstrate marked improvements in their sensory processing and practical competencies, which are critical for their overall readiness to advance in more formal educational settings. The findings underscore the long-term benefits of integrating Montessori principles into early childhood education, suggesting that these methods not only prepare children for academic success but also contribute to their holistic development, equipping them with the skills needed to navigate the complexities of everyday life.